Spectroscopic constants and transition properties of the SnH+ ion excited states including spin-orbit coupling. (February 2023) - Liu, Yahong; Xiao, Zhiyu; Liu, Yong; Minaev, Boris; Panchenko, Alexandr; Yan, Bing
Highlights: The high-level ab initio calculation is performed on SnH + with the spin-orbit coupling effect. And the states correlated with charge-exchange atomic limit are included in this work. Potential energy curves and spectroscopic constants for bound states of SnH + are obtained. The transitions properties of A 1 Π1 - a 3 Π0±, 1, 2 and 1(Ⅲ) - X 1 Σ + 0+ vibronic bands are predicted. Abstract: A high-level ab initio calculation on the electronic states of SnH + is carried out using multi-reference configuration interaction method (MRCI) in combination with Davidson correction (+ Q ) and spin-orbit coupling (SOC) effects. The potential energy curves (PECs) of the 21 Λ-S states correlated with six dissociation limits, as well as those of the lowest 31 Ω states generated from the Λ-S states under the SOC effect account are presented. Especially, the states correlated with charge-exchange atomic limit are included in this work. The spectroscopic constants of the bound states are determined, which are in accordance with the available theoretical and experimental results. The transition dipole moments distance dependence, Franck-Condon factors and the radiative lifetimes of the selected transitions are calculated and discussed. In particular, the A 1 Π1 - a 3 Π0±, 1, 2 and 1(Ⅲ) - X 1 Σ + 0+ vibronic bands are predicted. This study is expected to be useful for further interpretation of the detailed electronic spectra of the SnH + species, as well as complicated rovibronic bands of the other group-IV monohydride cations.